Strategi Manajemen Menggunakan Analisis SWOT Pada Usaha UMKM (Studi Usaha Angkringan Sedulur) - Farhan, Reizy; Hasbullah, Hasbullah; Hidayahtullah, Rahmad; Pangestu, Yog; Suci, Rama Gita (Jurnal Bisnis, Manajemen, dan Ekonomi, 2024)
Angkringan businesses are widespread and attract many customers because of their wide market reach. Marketing strategies are used to determine business products to get the desired results. Actions that can be taken are SWOT analysis. This research aims to determine strategic management SWOT analysis with strategic management using Porter's Five Force theory. Qualitative methodology is used in the research process. Data collection techniques include interviews and observation. Based on the research results and discussion of marketing strategies using SWOT analysis on angkringan sedulur, including strengths (strengths) by providing games, free wifi and spacious parking and an online marketing system or social media. The weakness is that if it rains, there are only a few seats for shelter and many other angkringan competitors at that location. Opportunities are a strategic location in the middle of the city and next to hotels and the trendy Angkringan style, which is a busy place to hang out. Based on Porter's Five Forces theory, the strategies carried out are building a brand image, increasing product differentiation, choosing quality raw materials, offering games, free WiFi and a large parking area, maintaining the products’ quality, and charging cheaper rates than competitors.